การศึกษาสวัสดิการของแรงงานระดับหน่วยผลิตนิคมอุตสาหกรรมภาคเหนือ จังหวัดลำพูน - วสันติ์ คำบุรี (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The purposes of the study were to investigate and to study the satisfaction of the labor’s non-enforcement welfares toward the production level labors of overseas-invested corporations in comparison with those of domestically-invested corporations. The samples were divided into two groups: 50 entrepreneurs and 400 production level laborers. Questionnaires were used to collect data which were then analyzed by descriptive statistics, Likert-type scales and t-test. It was found that most entrepreneurs of the overseas-invested corporations were Japanese nationals and there were an average of 1,227 laborers in each corporation. Most entrepreneurs of the domestically-invested corporations were Thai nationals and there were an average of 705 laborers in each corporation. The respondents were those working in the human resource department and in charge of providing the welfares for the laborers. Both overseas-invested corporations and domestically-invested corporations provided 6 labor’s non-enforcement welfares. The largest welfares provided were recreation and health. The difference of welfare allocation between both corporations was the saving for the laborers in terms of providence fund. The majority of the 400 production level laborers were female with an average age of 38. 57.50% were single. They were native to the northern region. They possessed the bachelor degree with an average of 5-year experience. Their job included assembling the assembly parts and quality controlling. They earned an average monthly salary of 10,087 baht. Besides, the labors of overseas and domestic corporation both were similarly provided with 6 additional welfares. However, both were differently provided with stipendiary welfare including bonus, stipend, incentive, shift fee. The laborers were highly satisfied with three labor’s non-enforcement welfares: providence fund, stipend, recreation and health respectively. It can be concluded that the laborers do not recognize that they are provided with labor’s non-enforcement welfares. This is probably because they are not well informed about labor’s non-enforcement welfares from their corporations which lack good public relations.